PERSONALIZATION OF TREATMENT AND PREVENTION TACTICS IN THE EARLY STAGES OF AVASCULAR NECROSIS OF THE HIP BONE BASED ON CLINICAL AND GENETIC PROFILING (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Avascular necrosis of the femoral head (ANFH) is a progressive degenerative-dystrophic disease that leads to persistent pain, limited mobility, and a significant decrease in the quality of life in patients of working age. The traditional assessment of patients' condition, which is based primarily on the radiological characteristics of the disease stage, does not always allow for predicting the rate of progression and the individual response to conservative therapy. Therefore, the integration of molecular genetic parameters into the algorithms for selecting treatment and rehabilitation strategies is of particular interest. One of the promising areas is the study of PPARγ gene polymorphism, which is associated with lipid metabolism, osteogenesis, and bone remodeling, and may have a direct impact on the course of ANFH and the effectiveness of early pathogenetic intervention.